A self-pulsing ring cavity ultra-long Raman fiber laser - Muhd Zamani, Zulkifli; K. Y., Lau; H., Kbashi; Moh, Yasin; M. A., Mahdi (IOP Publishing, 2018)
Ultra-long Raman fiber lasers are of significant interest due to their application in the telecommunications industry. In this work we propose a self-pulsing ultra-long Raman fiber laser with a ring cavity configuration. A TrueWave® REACH fiber is deployed as the gain medium for the Raman fiber laser. Three laser cavities with different total cavity lengths are investigated; these generate pulse repetition rates of approximately 25 MHz, 14 MHz and 10 MHz for TrueWave® REACH fibers of lengths 28 km, 56 km and 76 km, respectively. With a similar pump power of 2.48 W a broader spectral bandwidth is observed for the shorter laser cavity. The highest signal-to-noise ratios of 46 dB and 47 dB are attained for laser cavities with 56 km and 76 km TrueWave® REACH fibers at pump powers of 1.62 W and 1.97 W, respectively. This work differs from previous works which mostly employed a linear laser cavity configuration and other gain media to obtain a self-pulsing Raman fiber laser.